ANALYSIS OF THE CAUSALITY OF CO2 EMISSIONS, CONSUMPTION OF FOSSIL FUELS, ELECTRICITY CONSUMPTION, AND ECONOMIC GROWTH IN INDONESIA IN 1990-2019 - Melati Intan Kurnia; Hadi Sasana; Yustirania Septiani (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2019)
Increasing economic growth will spark against increased energy consumption. But on the other hand, increasing economic growth will also trigger the occurrence of natural damage and degradation of environmental quality derived from CO2 emissions. CO2 emissions are caused by oxidation process of fossil fuel energy. This research aims to know the causality relationship between CO2 emissions, fossil fuel consumption, electricity consumption, and economic growth in Indonesia, as well as long-term relationship between CO2 emissions, fossil fuel consumption, electricity consumption, to economic growth in Indonesia in 1990 – 2019. The used data is the secondary data that is in the form of data time series. The dependent variables of this study are economic growth, while independent variables are CO2 emissions, fossil fuel consumption, electricity consumption. The method that is used in this study is Vector Error Correction Model. The results showed that there was a one-way causality between economic growth and fossil fuel consumption, and between electricity consumption and CO2 emissions. The research also shows that on long-term CO2 emissions has a negative influence, while the consumption of fossil fuels and electricity has a positive effect on Indonesia's economic growth in 1990-2019.Keywords: CO2, Energy Consumption, Economic Growth.